PEMBERDAYAAN MASYARAKAT MELALUI EDUKASI PENGELOLAAN SAMPAH DI BANJAR BELALUAN, DESA SINGAPADU TENGAH - Ni Kadek Intan Karunia Dewi; I Putu Gede Satria Wibawa; Mansuetus Ganti; Ni Made Sri Maharani; I Gusti Ayu Rai; Ni Luh Putu Indrawathi (LP3M Universitas PGRI Mahadewa Indonesia, 2026)
Waste problems at the household level often stem from a lack of community knowledge in classifying waste types and a low awareness of the economic value of such waste. The background of this research is the environmental situation in Banjar Belaluan, Central Singapadu, where waste management is still carried out traditionally and without segregation. This study aims to explain the process of community empowerment through learning how to sort waste and process organic, inorganic, and residual waste into products with economic value. The method used in this study is descriptive qualitative with a participatory action approach, in which researchers participated in providing technical training to the local community. The findings of this study indicate that through systematic education, the community has been able to sort waste at its source and understand the characteristics of residual waste that needs to be disposed of. Furthermore, residents have successfully processed organic waste into fertilizer and transformed inorganic waste, such as plastic, into creative crafts such as key chains and other accessories. This integration of empowerment not only impacts the environmental cleanliness of the banjar but also creates opportunities for developing a creative economy focused on waste management. People now view waste not as worthless waste, but as a valuable asset that can be transformed into a source of additional income for families through sustainable creativity and innovation.